Jonas Mašiotas the mathematics teacher - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2021)
Mathematics teacher Jonas Mašiotas (1897–1953) was the son of Pranas Mašiotas (1863–1940) – the famous Lithuania author of mathematical coursebooks and didactic articles as well as the a creator of books for children. JonasMašiotas studied mathematics in Germany and Switzerland. Prior to the studies, he was engaged as a teacher in Marijampol˙e, after completion of the studies – in Kaunas and during the World War II – in Vilkija. He published 2 articles in didactics of mathematics and 5 coursebooks (including one that consisted of 7 parts), edited and published the coursebook in trigonometry prepared by his father P. Mašiotas. He was one of the enthusiasts for introducing the concept of a function into the school curriculum in mathematics.